Elevator game [videorecording (DVD)] - Anania, Gino; Best, Megan; Carlos, Alec (Shudder, 2023)
Supernatural horror, based on the eponymous online phenomenon, is a ritual conducted in an elevator, in which players attempt to travel to another dimension using a set of rules that can be found online.